PLAC8 promotes the autophagic activity and improves the growth priority of human trophoblast cells. Issue 3 (11th February 2021) - Feng, Xuan; Wei, Zhi; Tao, Xiang; Du, Yan; Wu, Jing; Yu, Yinhua; Yu, Huandi; Zhao, Hongbo
Abstract: Autophagy plays an important role in the normal development and function of trophoblast cells and is precisely regulated during pregnancy. Dysregulated autophagy contributes to the abnormal proliferation of trophoblasts, which is closely related to the occurrence of pregnancy‐related diseases. Placenta specific 8 (PLAC8, Onzin) is a multifaceted protein proven to promote autophagy and potentiate various tumor progression. Its role in trophoblasts remains elusive. In our present study, PLAC8 expression was detected in tissues of first‐trimester placentas (n = 5), term placentas (n = 5), choriocarcinoma (n = 5), and placental site trophoblastic tumor (n = 5). PLAC8 expression was increased in gestational neoplasms compared with normal pregnancies. mCherry‐EGFP‐LC3B reporter and transmission electron microscopy confirmed PLAC8 promoted the autophagic flux of human trophoblast cells. Both gain‐of‐function and loss‐of‐function experiments demonstrated PLAC8‐regulated autophagy‐related genes, including ATG5, ATG12, and Beclin‐1. In addition, our data showed that PLAC8 co‐localized with p53 and promoted its degradation, and p53 re‐expression partially abrogated the PLAC8‐induced autophagy activity. Furthermore, the overexpression of PLAC8 promoted cell viability and proliferation, acting as a protective mechanism of trophoblasts against the cytotoxicity of etoposide (VP‐16). Such a phenomenon was effectively abrogated by autophagy inhibitors 3‐methyladenine (3‐MA) and chloroquine (CQ). In conclusion, PLAC8‐induced autophagy to promote the proliferation of trophoblasts. This study provided insights into the mechanism of PLAC8‐induced autophagy in trophoblasts, which is significant for a wide range of gestational diseases and may contribute to developing novel treatment strategies for trophoblastic diseases.